Impact Analysis of TikTok Application Usage on the Emotional Development of Early Childhood at ABA 39 Kindergarten, Malang City - Syahrani Nabilah; Tomas Iriyanto; Munaisra Tirtaningsih (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The rapid development of digital technology in the Industrial Revolution 4.0 era has increased smartphone and social media usage, including TikTok, among early childhood. This study aims to analyze the impact of TikTok application usage on the emotional development of early childhood at TK ABA 39 Malang City. This research employed a descriptive qualitative approach using observation and in-depth interviews as data collection techniques. The research subjects consisted of three teachers and three parents of children aged 5–6 years. The study was conducted in July 2024 at TK ABA 39 Malang City. The findings indicate that TikTok usage has positive impacts, such as enhancing children’s self-expression, creativity, confidence, and the development of empathy and sympathy when children access age-appropriate content under adult supervision. However, negative impacts were also identified, including emotional instability, decreased focus, and resistant behavior when screen time was restricted. Therefore, it can be concluded that TikTok usage has a significant influence on early childhood emotional development. Active supervision, guidance, and digital literacy education from parents and teachers are essential to ensure that TikTok is used wisely to support healthy and balanced emotional development in early childhood.